2022
DOI: 10.1002/ana.26547
|View full text |Cite
|
Sign up to set email alerts
|

Tenecteplase Improves Reperfusion across Time in Large Vessel Stroke

Abstract: Objective Tenecteplase improves reperfusion compared to alteplase in patients with large vessel occlusions. To determine whether this improvement varies across the spectrum of thrombolytic agent to reperfusion assessment times, we performed a comparative analysis of tenecteplase and alteplase reperfusion rates. Methods Patients with large vessel occlusion and treatment with thrombolysis were pooled from the Melbourne Stroke Registry, and the EXTEND‐IA and EXTEND‐IA TNK trials. The primary outcome, thrombolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Early recanalization rates with alteplase in this study are similar to those reported in the Identifying New Approaches to Optimize Thrombus Characterization for Predicting Early Recanalization and Reperfusion With IV Alteplase and Other Treatments Using Serial CT Angiography (INTERRSECT) study 5 (ie, 13%). These findings are also consistent with a French multicenter study 7 of 262 patients and the pooled analysis 21 of EXTEND IA and EXTEND IA TNK trials and the Melbourne Stroke Registry, which found similar rates of early reperfusion in both thrombolytic agents (21% vs 18% and 21% vs 19%, respectively). A large proportion of patients in these studies were transferred from a primary stroke center (drip-and-ship paradigm) and had long times from thrombolytic administration to reperfusion assessment.…”
Section: Common Odds Ratio Is the Odds Ratio For A 1-unit Increase In...supporting
confidence: 90%
See 4 more Smart Citations
“…Early recanalization rates with alteplase in this study are similar to those reported in the Identifying New Approaches to Optimize Thrombus Characterization for Predicting Early Recanalization and Reperfusion With IV Alteplase and Other Treatments Using Serial CT Angiography (INTERRSECT) study 5 (ie, 13%). These findings are also consistent with a French multicenter study 7 of 262 patients and the pooled analysis 21 of EXTEND IA and EXTEND IA TNK trials and the Melbourne Stroke Registry, which found similar rates of early reperfusion in both thrombolytic agents (21% vs 18% and 21% vs 19%, respectively). A large proportion of patients in these studies were transferred from a primary stroke center (drip-and-ship paradigm) and had long times from thrombolytic administration to reperfusion assessment.…”
Section: Common Odds Ratio Is the Odds Ratio For A 1-unit Increase In...supporting
confidence: 90%
“…This has potentially contributed to the higher reperfusion rates overall for both thrombolytic agents and for the reported difference between treatment groups . Of note, median (IQR) time from thrombolysis to reperfusion assessment in our study was 53 (35-77) minutes (Table 1) vs 76 (48-125) minutes in the pooled Australian data . The differences in early recanalization vs early reperfusion rates in this study are expected, as thrombolysis could result in thrombus migration to major distal branches without corresponding improvement in reperfusion, especially soon after lytic administration .…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations